Controlling the cost of social security - Daly, John Charles; Conable, Barber B.; American Enterprise Institute for Public Policy Research (Washington, D.C. : The American Enterprise Institute for Public Policy Research, 1981)
Examines the immediate and long-term problems facing the social security system and the legislation proposed to solve them.
Held on June 25, 1981 and sponsored by the American Enterprise Institute for Public Policy Research.
oif 08/04/2019
Loans
Keywords: Social security--Cost; United States